A recyclable cobalt(iii)–ammonia complex catalyst for catalytic epoxidation of olefins with air as the oxidant. (19th January 2021) - Wang, Chenlong; Zhan, Hongju; Lu, Xinhuan; Jing, Run; Zhang, Haifu; Yang, Lu; Li, Xixi; Yue, Fanfan; Zhou, Dan; Xia, Qinghua
Abstract : A recyclable [Co(NH3 )6 ]Cl3 complex was synthesized to catalyze the epoxidation of α-pinene. With air as the oxidant, [Co(NH3 )6 ]Cl3 obtained 97.4% conversion of α-pinene and 98.3% selectivity of epoxide. Abstract : [Co(NH3 )6 ]Cl3 and other ammonia complexes with different external anions or metal ions were synthesized to catalyze the epoxidation of α-pinene. The synthesized complexes were characterized using XRD, SEM, TGA, FTIR and UV spectra. With air as the oxidant, [Co(NH3 )6 ]Cl3 exhibited excellent catalytic activity for the epoxidation of α-pinene among the prepared complexes. The conversion of α-pinene reached 97.4%, with 98.3% selectivity of epoxide when using a small amount of cumene hydroperoxide (CHP) as the initiator. The results revealed that a single Co(iii ) system can also catalyze the epoxidation process in the absence of Co(ii ), even showing better catalytic performance than single Co(ii ). Recycling experiments showed that there was no significant drop in activity after 10 cycles, demonstrating that it is a stable and efficient heterogeneous catalyst for the epoxidation of α-pinene. The excellent recycling performance may be attributed to the stability of the coordination complex itself.